“Green” construction as a promising direction for the development of small entrepreneurship in Ukraine (Economics and region, 2021)
The article is devoted to the topical issue of introducing the technology of "green" construction. The basic principles on the basis of which ecological construction is carried out are considered. The experience of some construction companies in Ukraine is analyzed. Today, "green" construction in Ukraine is at an early stage of development. Therefore, it is one of the promising areas for the development of a small enterprise entity. A business plan for the construction of low-rise wooden houses has been drawn up and proposed for implementation. This can become one of the ways for the development of small entrepreneurship in Ukraine.
Keywords: entrepreneurship; small enterprise; ecological construction; development